The application of a synthetic biodegradable temporizing matrix in extensive burn injury: a unicenter experience of 175 cases - Tapking, Christian; Panayi, Adriana C.; Hundeshagen, Gabriel; Thomas, Benjamin; Gazyakan, Emre; Bliesener, Björn; Bigdeli, Amir Khosrow; Kneser, Ulrich; Vollbach, Felix Hubertus (Journal of Clinical Medicine, 2024)
Objectives: Addressing extensive and deep burn wounds poses considerable challenges for both patients and surgeons. The NovoSorb® Biodegradable Temporizing Matrix (BTM) emerged as a novel dermal substitute and has been subjected to evaluation in large burn wound cases, with a specific focus on identifying risk factors associated with suboptimal take rates. Methods: All patients with burn wounds greater than 10% body surface that underwent BTM treatment between March 2020 and November 2023 were eligible for inclusion. Univariate analyses and linear regression models were employed to discern risk factors and predictors influencing the take rates of both the BTM and split-thickness skin grafts (STSGs). Results: A total of 175 patients (mean age 56.2 ± 19.8 years, 70.3% male) were evaluated. The mean take rates of the BTM and STSGs were 82.0 ± 24.7% and 87.3 ± 19.0%, respectively. There were significant negative correlations between BTM take and the number of surgeries before BTM application (r = −0.19, p = 0.01), %TBSA and STSG take (r = −0.36, p = <0.001) and significant positive correlations between BTM and STSG take (r = 0.41, p ≤ 0.001) in addition to NPWT and STSG take (r = 0.21, p = 0.01). Multivariate regression analyses showed that a larger number of surgeries prior to BTM application (OR −3.41, 95% CI −6.82, −0.03, p = 0.04) was associated with poorer BTM take. Allograft treatment before BTM application (OR −14.7, 95% CI −23.0, −6.43,p = 0.01) and failed treatment with STSG before BTM application (OR −20.8, 95% CI −36.3, −5.23, p ≤ 0.01) were associated with poorer STSG take, whereas higher BTM take rates were associated with overall higher STSG take (OR −0.15, 95% 0.05, 0.26, p = 0.01). The Meek technique was used in 24 patients and showed similar take rates (BTM: 76.3 ± 28.0%, p = 0.22; STSG: 80.7 ± 21.1, p = 0.07). Conclusions: This study summarizes our findings on the application of a BTM in the context of large burn wounds. The results demonstrate that successful treatment can be achieved even in patients with extensive burns, resulting in satisfying take rates for both the BTM and STSG. The data underscore the importance of promptly applying a BTM to debrided wounds and indicate good results when using Meek.
Gesehen am 30.09.2024